Research funding impact and priority setting - advancing universal access and quality healthcare research in Malaysia - Weng Hong Fun; Sondi Sararaks; Ee Hong Tan; Kar Foong Tang; Diane Woei Quan Chong; Lee Lan Low; Roslinda Abu Sapian; S. Asmaliza Ismail; Suresh Kumar Govind; Siti Haniza Mahmud; Shahnaz Murad (BMC, 2019)
Abstract Background Health Research Priority Setting (HRPS) in the Ministry of Health (MOH) Malaysia was initiated more than a decade ago to drive effort toward research for informed decision and policy-making. This study assessed the impact of funded prioritised research and identified research gaps to inform future priority setting initiatives for universal access and quality healthcare in Malaysia. Methods Research impact of universal access and quality healthcare projects funded by the National Institutes of Health Malaysia were assessed based on the modified Payback Framework, addressing categories of informing policy, knowledge production, and benefits to health and health sector. For the HRPS process, the Child Health and Nutrition Research Initiative methodology was adapted and adopted, with the incorporation of stakeholder values using weights and monetary allocation survey. Workshop discussions and interviews with stakeholders and research groups were conducted to identify research gaps, with the use of conceptual frameworks to guide the search. Results Seventeen ongoing and 50 completed projects were identified for research funding impact analysis. Overall, research fund allocation differed from stakeholders' expectation. For research impact, 48 out of 50 completed projects (96.0%) contributed to some form of policy-making efforts. Almost all completed projects resulted in outputs that contributed to knowledge production and were expected to lead to health and health sector benefits. The HRPS process led to the identification of research priority areas that stemmed from ongoing and new issues identified for universal access and quality healthcare. Conclusion The concerted efforts of evaluation of research funding impact, prioritisation, dissemination and policy-maker involvement were valuable for optimal health research resource utilisation in a resource constrained developing country. Embedding impact evaluation into a priority setting process and funding research based on national needs could facilitate health research investment to reach its potential.